2016
DOI: 10.1155/2016/3574149
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Microbial Load and Profile of Potential Pathogens and Food Spoilage Bacteria from Household Kitchen Tables

Abstract: The aim was to study the bacterial load and isolate potential pathogens and food spoilage bacteria from kitchen tables, including preparation tables and dining tables. Methods. A total of 53 households gave their consent for participation. The samples were collected by swabbing over an area of 5 cm by 5 cm of the tables and processed for bacterial count which was read as colony forming units (CFU), followed by isolation and identification of potential pathogens and food spoilage bacteria. Result. Knowledge abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Observation from the study indicated that samples obtained from producers were relatively high in the three isolates especially Staphylococcus aureus due to compromise in food safety standards. This result is similar to reports on prevalence of microbes associated with production, environment and persons involved with production of food (Adu-Gyam et al 2012;Biranjia-Hurdoyal and Latouche 2016).…”
Section: Distribution Of Bacteria Based On the Product Chainsupporting
confidence: 90%
“…Observation from the study indicated that samples obtained from producers were relatively high in the three isolates especially Staphylococcus aureus due to compromise in food safety standards. This result is similar to reports on prevalence of microbes associated with production, environment and persons involved with production of food (Adu-Gyam et al 2012;Biranjia-Hurdoyal and Latouche 2016).…”
Section: Distribution Of Bacteria Based On the Product Chainsupporting
confidence: 90%
“…Several reports have been indicated that food-borne diseases are a global problem [4, 5]. Contaminated food causes 1.5 billion cases of diarrhea in children annually, leading to more than 3 million deaths all over the world [3, 6, 7]. Considering the key role of the kitchen in transmitting pathogens to food and the role of food in transmitting the diseases to humans, we can realize its importance.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 40 years, many studies have aimed to assess the degree of microbial contamination of different kitchen surfaces and objects and if the identified pathogens can be the cause of food-borne diseases, as well as to find a correlation between respecting or not some properly inhome hygiene practices and the onset of these morbid entities [6,36,17,41]. Moreover, Romania reported that in 1999-2000, 94% of food-borne illnesses occurred in the domestic environment [42].…”
Section: Resultsmentioning
confidence: 99%